An exploratory survey method for archaeoastronomy, applied to standing stones at the hauviri and taputapuātea maraes, Ra'iātea. (April 2018) - Goodwin, David
Abstract: Polynesia has a vast area, and surveys are few and unsystematic. Rapid, low-cost and personnel surveys are needed to identify cases that merit an in-depth treatment. However, surveying options are limited, especially where relative positions of objects and the azimuths between them are important. In this article, a survey method is tested on standing stones at the Taputāpuatea and Hauviri maraes, Ra 'iātea. The resulting data set was used to test three hypotheses, namely: the stones line up with voyage destinations, or commemorate significant voyages; stones form an analogue "star compass" of directions where significant navigational stars rise and set; and stones line up with important stars at a significant epoch of the year. The surveys yielded a data set that benchmarks stone positions at the time of survey, is capable of fairly accurate azimuth comparisons, and is sufficiently rich to be mined in different ways in subsequent research. One situation at the season of Matariki in AD1250 is identified for further investigation. Highlights: Polynesia has a vast area, and surveys are few and unsystematic. Low-cost and personnel surveys are needed to identify cases for in-depth treatment. This is especially so where relative positions and azimuths are important. A survey method is tested on the Taputapuate and Hauviri maraes, Ra'iātea. One situation at Matariki in 1250 CE is identified for further investigation.